Pluralisme Agama dalam Prespektif Nurcholish Madjid - Purwanto, Purwanto (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
It is an interesting to see how religious pluralism thrives and well applied in Indonesia. One plus point for such matter is as a response toward inter-religious tolerance in Indonesia in the latest period. Nurcholish Madjid is one of Muslim intellectualist who gives declarations on the religious pluralism concept in Indonesia. He is also known as the one who brings pluralism in observing issues relating to inter-religious relationship. His perspective of pluralism is wrapped in the context of Islamism, Indonesianism and modernism which is very interesting to review it. For one case, he takes into account religious pluralism based on Islamic point of view which is full of egalitarianism, opened and just. The idea of Nurcholish Madjid’s pluralism focuses on tawhîd, in the context of philological and historical subject. It is to openly differentiate between the realm of God and the reality of mankind. Philological perspective comes from the process of redefining meaning of Islâm in Arabic language as “surrender” and “submission”, while the historical perspective comes with a number of facts in the history of religious plurality. This basic idea will initiate religious relativism, religious similarity, and religious freedom. Madjid’s idea allows Islam to view other religions and religious diversities. It is a universal vision: from exclusivism to inclusivism. Madjid’s opinion could be seen as intellectual concern to the realm of religious life. This article attempts to explore Madjid’s idea on religious pluralism